VEGF-A Regulates Cellular Localization of SR-BI as Well as Transendothelial Transport of HDL but Not LDL. Issue 5 (May 2017) - Velagapudi, Srividya; Yalcinkaya, Mustafa; Piemontese, Antonio; Meier, Roger; Nørrelykke, Simon Flyvbjerg; Perisa, Damir; Rzepiela, Andrzej; Stebler, Michael; Stoma, Szymon; Zanoni, Paolo; Rohrer, Lucia; von Eckardstein, Arnold
Abstract : Objective—: Low- and high-density lipoproteins (LDL and HDL) must pass the endothelial layer to exert pro- and antiatherogenic activities, respectively, within the vascular wall. However, the rate-limiting factors that mediate transendothelial transport of lipoproteins are yet little known. Therefore, we performed a high-throughput screen with kinase drug inhibitors to identify modulators of transendothelial LDL and HDL transport. Approach and Results—: Microscopy-based high-content screening was performed by incubating human aortic endothelial cells with 141 kinase-inhibiting drugs and fluorescent-labeled LDL or HDL. Inhibitors of vascular endothelial growth factor (VEGF) receptors (VEGFR) significantly decreased the uptake of HDL but not LDL. Silencing of VEGF receptor 2 significantly decreased cellular binding, association, and transendothelial transport of 125 I-HDL but not 125 I-LDL. RNA interference with VEGF receptor 1 or VEGF receptor 3 had no effect. Binding, uptake, and transport of HDL but not LDL were strongly reduced in the absence of VEGF-A from the cell culture medium and were restored by the addition of VEGF-A. The restoring effect of VEGF-A on endothelial binding, uptake, and transport of HDL was abrogated by pharmacological inhibition of phosphatidyl-inositol 3 kinase/protein kinase B or p38 mitogen-activated protein kinase, as well as silencing of scavenger receptor BI. Moreover, the presence of VEGF-A was found to be a prerequisite for the localization of scavenger receptor BI in the plasma membrane of endothelial cells. Conclusions—: The identification of VEGF as a regulatory factor of transendothelial transport of HDL but not LDL supports the concept that the endothelium is a specific and, hence, druggable barrier for the entry of lipoproteins into the vascular wall. Abstract : Supplemental Digital Content is available in the text.